Legal Status, Role and Features of Electronic Document Management. / Estado legal, función y características de la gestión de documentos electrónicos. - GIORGIEVICH OKRIASHVILI, TIMUR; GUMAROVICH YAKUPOV, ALBERT; VALENTINOVICH PAVLYUK, ALBERT; ANATOLYEVNA KIRILLOVA, ELENA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study analyses the conditions and the degree of development of approaches to the legal regulation of electronic document management and the possibility of introducing this management in various areas at the international level.The study concluded that for the full implementation of electronic document management at the international level, it is necessary to create a trust service, which is an intermediary link with the powers and rights to verify the authenticity of electronic signatures and the legitimacy of digital documents. This will fully allow the use of the capabilities of telecommunication systems and electronic document management. RESUMEN El estudio analiza las condiciones y el grado de desarrollo de los enfoques de la regulación legal de la gestión de documentos electrónicos y la posibilidad de introducir esta gestión en diversas áreas a nivel internacional. El estudio concluyó que, para la plena implementación de la gestión documental electrónica a nivel internacional, es necesario crear un servicio de confianza, que es un vínculo intermediario con las facultades y derechos para verificar la autenticidad de las firmas electrónicas y la legitimidad de los documentos digitales. Esto permitirá utilizar plenamente las capacidades de los sistemas de telecomunicaciones y la gestión de documentos electrónicos.